Infomusa: The international magazine on banana and plantain: Vol. 13(2) - International Network for the Improvement of Banana and Plantain (2004)
The first two days of the First International Congress on Musa featured presentations from breeders, geneticists and molecular scientists with a session on genetic resources and improvement and the 4th International symposium on the molecular and cellular biology of bananas. Kodjo Tomekpe, head breeder and director of the Centre Africain de Recherches sur Bananiers et Plantains (CARBAP) opened the Congress with a review on conventional breeding strategies (see article on p. 2), their achievements but also their limitations.